2021
DOI: 10.1097/aud.0000000000001182
|View full text |Cite
|
Sign up to set email alerts
|

Bilinguals Show Proportionally Greater Benefit From Visual Speech Cues and Sentence Context in Their Second Compared to Their First Language

Abstract: Objectives: Speech perception in noise is challenging, but evidence suggests that it may be facilitated by visual speech cues (e.g., lip movements) and supportive sentence context in native speakers. Comparatively few studies have investigated speech perception in noise in bilinguals, and little is known about the impact of visual speech cues and supportive sentence context in a first language compared to a second language within the same individual. The current study addresses this gap by directly investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Furthermore, these results add to a growing literature suggesting that bilinguals benefit from visual speech cues (e.g., Chauvin & Phillips, 2022) and sentence context (e.g., Kousaie et al, 2019) in their L2. Additionally, the current results extend this further to suggest that both younger and older bilinguals can benefit from visual speech cues and sentence context in L2, although the benefit of visual speech cues in L2 was somewhat smaller in older adults compared to young adults.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, these results add to a growing literature suggesting that bilinguals benefit from visual speech cues (e.g., Chauvin & Phillips, 2022) and sentence context (e.g., Kousaie et al, 2019) in their L2. Additionally, the current results extend this further to suggest that both younger and older bilinguals can benefit from visual speech cues and sentence context in L2, although the benefit of visual speech cues in L2 was somewhat smaller in older adults compared to young adults.…”
Section: Discussionsupporting
confidence: 65%
“…Given that overall performance was equated in the baseline condition for both young and older bilinguals, we expect to find comparable effects of context across the age groups, as seen in Dubno et al (2000) and Buss et al (2019). Additionally, based on the results from Chauvin and Phillips (2022), we hypothesize that the benefit from visual speech cue and sentence context will be proportionally greater in L2 compared to L1 for both age groups.…”
Section: Speech In Noise In Young and Old Bilingualsmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the aforementioned studies in speech perception have focused on auditory experience, language experience is a multimodal event that not only involves auditory experience, but also modifies the visual environment. Past studies have demonstrated that more so than monolingual learners, bilingual learners are more dependent on visual information in language input (Chauvin & Phillips, 2022; Sebastián-Gallés et al, 2012), raising the possibility that visual information may be harnessed to a greater extent in bilingual learners. As a result, we would expect effects of bilingualism on perception and learning to span the different modalities within which language presents itself.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Krizman et al (2017) showed that bilinguals performed worse when perceiving sentences in noise in their L2 compared to monolinguals, whereas bilinguals performed better than monolinguals at perceiving tones in noise, suggesting that effects of acoustic degradation on L2 speech comprehension are dependent on linguistic knowledge. In contrast, other research has shown that bilinguals may benefit from a contextually supportive sentence context to a greater extent in their L2 compared to their L1 when listening to speech-in-noise ( Chauvin and Phillips, in press ).…”
Section: Introductionmentioning
confidence: 93%